Google Workspace for Education: імплементація в освітній процес - Терещук, Сергій Іванович; Tereshchuk, Serhii; Шаров, Сергій Володимирович; Sharov, Sergii (My University, 2024)
UA: У статті розглядається платформа Google Workspace for Education та її можливості для підтримки освітнього процесу у вищій школі. Розкрито можливості окремих онлайн сервісів Google (Classroom, Meet, Drive, Docs, Forms та ін.), які сприяють організації дистанційного та змішаного навчання. Висвітлено переваги Google Workspace, умови ефективного використання хмарних технологій. Наголошується на необхідності правильного підбору онлайн інструментів в залежності від освітньої мети, навчання учасників освітнього процесу інструментам Google, популяризацію їх можливостей. /// EN: The article examines the Google Workspace for Education platform and its possibilities for supporting the educational process in higher education. The capabilities of individual Google online services (Classroom, Meet, Drive, Docs, Forms, etc.) that contribute to the organization of distance and mixed learning are revealed. The advantages of Google Workspace, conditions for effective use of cloud technologies are highlighted. Emphasis is placed on the need for the correct selection of online tools depending on the educational goal, training participants in the educational process in Google tools, popularizing their capabilities.
Keywords: Google Workspace for Education; освітній процес; дистанційне навчання; цифрові інструменти; хмарні технології; educational process; distance learning; digital tools; cloud technologies